2014 IEEE International Conference on Communications (ICC) 2014
DOI: 10.1109/icc.2014.6884163
|View full text |Cite
|
Sign up to set email alerts
|

On the MIMO capacity with residual transceiver hardware impairments

Abstract: Abstract-Radio-frequency (RF) impairments in the transceiver hardware of communication systems (e.g., phase noise (PN), high power amplifier (HPA) nonlinearities, or inphase/quadrature-phase (I/Q) imbalance) can severely degrade the performance of traditional multiple-input multiple-output (MIMO) systems. Although calibration algorithms can partially compensate these impairments, the remaining distortion still has substantial impact. Despite this, most prior works have not analyzed this type of distortion. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 22 publications
4
69
0
Order By: Relevance
“…Motivated by the EVM, we adopt the 'binoisy' channel model of [3]- [12], which includes also a transmit-side noise term; this is a convenient compromise between facilitating theoretical analysis and resorting to measurements or simulations. In a strict sense, additive noise is still only a simplified representation of complex nonlinear phenomena occurring due to hardware impairments, especially when considering their joint coupled effects or residual distortion after compensation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Motivated by the EVM, we adopt the 'binoisy' channel model of [3]- [12], which includes also a transmit-side noise term; this is a convenient compromise between facilitating theoretical analysis and resorting to measurements or simulations. In a strict sense, additive noise is still only a simplified representation of complex nonlinear phenomena occurring due to hardware impairments, especially when considering their joint coupled effects or residual distortion after compensation.…”
Section: Introductionmentioning
confidence: 99%
“…The key reference results for the present study are reported in [3]- [12]. These seminal works formulated the research niche around the binoisy channel model and established the baseline understanding of MIMO communication under EVM with numerical simulations and theoretical analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, (21) and (24) are inherently complicated formulas. Motivated by this, we confine the results between an upper and two lower bounds such that R lower ≤ R ≤ R upper .…”
Section: Boundsmentioning
confidence: 99%
“…An example is the phase noise, which accumulates within the channel coherence period [18], [26], [27]. On the other hand, the aggregate effect from many impairments can be described by an additive system model [15], [16], [23]- [28],…”
Section: Introductionmentioning
confidence: 99%